Power density comparison of multi-air gap axial flux permanent magnet motor for electric vehicle. Issue 1 (September 2020) - Tadjuddin, M; Hasanuddin, I; Fuadi, Z; Mukminin, A; Arief, M R
Abstract: Electric vehicles are a necessity now, especially in the future. The efficiency of electric vehicles continues to be improved, especially in the drive system or electric motor. One type of electric motor used in an electric vehicle that has high efficiency and power density is permanent magnet axial flux motor. This paper explains the comparison of power density on two designs of axial flux motor. A single and multi-air gap axial flux motors had been compared. The finite element method (FEM) simulation is used to determine the power and volume of those motors. The results presented that the two air gaps power density axial flux motors were 195, 3 W/kg while those multi air-gap motor with four air gaps had 283.6 W/kg. The results shoes that four air-gap has a bigger power density than two air-gaps.